Iterative reconstruction to preserve image quality and diagnostic accuracy at reduced radiation dose in coronary CT angiography: an intraindividual comparison - Yin, Wei-Hua; Lu, Bin; Li, Nan; Han, Lei; Hou, Zhi-Hui; Wu, Run-Ze; Wu, Yong-Jian; Niu, Hong-Xia; Jiang, Shi-Liang; Krazinski, Aleksander W; Ebersberger, Ullrich; Meinel, Felix G; et al. (JACC. Cardiovascular imaging, 2013)
This study sought to determine whether a 50%-reduced radiation dose protocol using iterative reconstruction (IR) preserves image quality and diagnostic accuracy at coronary computed tomography angiography (CTA) as compared with a routine dose protocol using traditional filtered back projection (FBP). IR techniques show promise to decrease radiation requirements at coronary CTA. No study has performed a direct head-to-head, intraindividual comparison of IR algorithms with FBP vis-à-vis diagnostic accuracy and radiation dose at coronary CTA. Sixty consecutive subjects (45 men, 53.3 ± 9.4 years of age) prospectively underwent coronary catheter angiography (CCA) and 2 coronary CTA scans. One coronary CTA acquisition used routine radiation dose settings and was reconstructed with FBP. For another scan, the tube current-time product was reduced by 50%, and data were reconstructed with IR. Studies were blindly and randomly interpreted. Image quality, radiation dose, and diagnostic accuracy were compared using CCA as the reference standard. Sensitivity and specificity for diagnosing ≥50% coronary artery stenosis on a per-segment level were 88.5% and 92.1% with FBP and 84.2% and 93.4% with IR, respectively. On a per-patient level, sensitivity and specificity were 100% and 93.1% with FBP and 96.8% and 89.7% with IR, respectively (all p > 0.05). With FBP versus IR, the area under the receiver-operating characteristic curve was 0.903 (95% confidence interval [CI]: 0.881 to 0.922) and 0.888 (95% CI: 0.864 to 0.909) on a per-segment level, and 0.966 (95% CI: 0.883 to 0.996) and 0.932 (95% CI: 0.836 to 0.981) on a per-patient level, respectively (p = 0.290 and 0.330). Compared with FBP, the iterative series showed no significant (p > 0.05) differences in image quality analyses. Median dose-length product was 52% lower for the IR protocol compared with the FBP protocol (109.00 [interquartile range: 82.00 to 172.50] mGy·cm vs. 52.00 [interquartile range: 39.00 to 84.00] mGy·cm, p < 0.001). Compared with a routine radiation dose FBP protocol, 50% reduced dose acquisition using IR preserves image quality and diagnostic accuracy at coronary CTA.